2021
DOI: 10.26501/jibm/2021.1101-011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dark Triads on employee’s Time Banditry Behavior: Moderating Role of Islamic Work Ethics

Abstract: Purpose: The present study scrutinizes the novel concept of time banditry in the Banking sector. The study examined the impact of dark triad personalities- Machiavellianism, Narcissism, and Psychopathy, on the Time Banditry behavior. Also, the study extends the research on Islamic work ethics (IWE), whether IWE attenuates the detrimental effect of dark triad personalities on time banditry. Methodology: The study utilizes the survey method for data collection using questionnaire. Data was collected from 204 emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The significant direct and indirect effect of PCB demonstrated that AS is associated with increased psychological contract breach, which, in turn, leads to a greater likelihood of engaging in CWBs, supporting the mediating role hypothesized in this study and findings align with Griep et al . (2022), and ul Shuja et al ., (2021). The findings underscore the importance of understanding the underlying mechanisms through which abusive supervision exerts its influence.…”
Section: Discussionmentioning
confidence: 95%
“…The significant direct and indirect effect of PCB demonstrated that AS is associated with increased psychological contract breach, which, in turn, leads to a greater likelihood of engaging in CWBs, supporting the mediating role hypothesized in this study and findings align with Griep et al . (2022), and ul Shuja et al ., (2021). The findings underscore the importance of understanding the underlying mechanisms through which abusive supervision exerts its influence.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Wilhau (2021) demonstrated that the three dark traits predicted social loafing and that these relations were buffered by the team member exchange. Likewise, ul Shuja et al (2021) showed that the dark traits were related to the time banditry behavior and that the work ethical context attenuated such relations.…”
Section: Discussionmentioning
confidence: 99%